Integration of Growth and Cell Size via the TOR Pathway and the Dot6 Transcription Factor in Candida albicans. Issue 2 (27th December 2018) - Chaillot, Julien; Tebbji, Faiza; Mallick, Jaideep; Sellam, Adnane
Abstract: In most species, size homeostasis appears to be exerted in late G1 phase as cells commit to division, called Start in yeast and the Restriction Point in metazoans. This size threshold couples cell growth to division, and, thereby, establishes long-term size homeostasis. Our former investigations have shown that hundreds of genes markedly altered cell size under homeostatic growth conditions in the opportunistic yeast Candida albicans, but surprisingly only few of these overlapped with size control genes in the budding yeast Saccharomyces cerevisiae . Here, we investigated one of the divergent potent size regulators in C. albicans, the Myb-like HTH transcription factor Dot6. Our data demonstrated that Dot6 is a negative regulator of Start, and also acts as a transcriptional activator of ribosome biogenesis ( Ribi ) genes. Genetic epistasis uncovered that Dot6 interacted with the master transcriptional regulator of the G1 machinery, SBF complex, but not with the Ribi and cell size regulators Sch9, Sfp1, and p38/Hog1. Dot6 was required for carbon-source modulation of cell size, and it is regulated at the level of nuclear localization by the TOR pathway. Our findings support a model where Dot6 acts as a hub that integrates growth cues directly via the TOR pathway to control the commitment to mitotic division at G1.